Trend Analysis of Head and Neck Neoplasms between 2012–2018 in Patients Residing in Al-Madinah, Saudi Arabia: A Retrospective Study - Alsharif, Maha T.; Alsharif, Alla T.; Krsoum, Majid A.; Aljohani, Mazen A.; Qadiri, Osama M.; Alharbi, Abdulkarim A.; Al-Maweri, Sadeq A.; Warnakulasuriya, Saman; Kassim, Saba (European Journal of Dentistry, 2021)
Objectives This study sought to present a view of head and neck neoplasms (HNN) prevalence with specific focus on sociodemographic determinants in Al-Madinah Province, Saudi Arabia.Materials and Methods This was a hospital-based retrospective study based on retrieval of histopathological data for a period of 6 years between 2012 and 2018. Data was collected from the archives of the Oral and Maxillofacial Pathology Laboratory at King Fahad Hospital (the only referral center for biopsy services) in Al-Madinah City.Statistical Analysis An independent t-test and/or nonparametric (Mann–Whitney U test, chi-squared test) tests were used to determine the differences between groups. Statistical significance was set at the p-value < 0.05.Results Out of 96 patients, a total of 58 patients had valid biopsy data with preoperative diagnosis. Over three quarters of the cases (n = 44) were benign with only 24% were malignant. Males were more likely to be diagnosed with a benign tumor than females (54.5 vs. 45.6%, respectively), and malignancy was also more common in males (64.3 vs. 24.1). A significant difference was found in relation to mean age of older patients who were more likely to be diagnosed with malignant tumors (p = 0.001).Conclusions The findings suggest that most of biopsied HNN cases are benign neoplasms. Age is a significant risk factor for head and neck malignancy in this region. Delays in diagnosis of HNN need to be explored.
Keywords: head and neck neoplasms; trend analysis; diagnostic delays; histopathology; Saudi Arabia